Wardha District Plan on Gandhian Lines Report of the Sub-Group - Planning Commission (Planning Commission, 1982)
The "Wardha District Plan on Gandhian Lines" presents a holistic development strategy aimed at eradicating poverty and promoting self-reliance through community participation. Anchored in Gandhian principles, the plan emphasizes employment generation for 80,000 families, health improvement, educational expansion, and infrastructure development, including roads and potable water supply. Key strategies involve agricultural enhancement, animal husbandry, vocational training, and environmental sanitation. The plan advocates a collaborative governance model, engaging government agencies, local communities, and technical experts, to ensure effective implementation, monitoring, and sustainable outcomes. By integrating Gandhian philosophy with contemporary development methods, the initiative positions Wardha as a model for rural development across India.
Planning Commission Government of India April 1982
Planning Commission Government of India April 1982
Keywords: Wardha District; Gandhian Principles; Rural Development; Employment Generation; Health Improvement; Education Enhancement; Infrastructure Development; Water Supply; Agricultural Development; Community Participation; Sustainable Development; Poverty Alleviation